Brain electrical activity in Newly diagnosed Generalized Anxiety Disorder: A Quantitative EEG analysis - Boby, Farjana; Lima, Marefa Tuz Zohora; Zaman, Nusrut; Afroz, Sharmin; Morshed, Nahid Mahjabin; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2024)
Background: Generalized Anxiety Disorder (GAD) is one of the most common global mental disorders with negative impact on social life. Quantitative EEG can objectively estimate the anxiety status. Relatively increase beta activity along with decrease alpha activity is associated with GAD. Objectives:To evaluate power of all brain waves in female patients with GAD. Methods:This observational study was conducted on 20 female patients with GAD (age 20-40 years),For comparison, 20 healthy female volunteers of same age were enrolled as control. In this study, EEG was recorded for 3 minutes by placing electrodes on scalp according to 10-20 system. To assess brain electrical activities, the band power of delta, theta, alpha and beta brainwave was recorded from an EEG data acquisition device, EEG Traveler Brain Tech 32+ CMEEG -01, India. Power spectral analysis of EEG data was done by BT40 analysis software. Data were expressed as median (Inter Quartile Range). Statistical analysis was done by Mann-Whitney U test.Results: The significantly higher absolute power of beta was found in most of the electrodes of prefrontal, frontal and temporal region as well as significantly lower power of alpha, theta and delta werefound in all cortical regions in female GAD patients compared to healthy controls at baseline. Conclusion: This study concluded that GAD patients had high excitable state in most of cortical region associated with lack of relaxing ability. J Bangladesh Soc Physiol 2023;18(2): 78-88